E-clinic : Developing an application to support activities of clinical personnel / Muhd Eizan Shafiq Abd Aziz - Abd Aziz, Muhd Eizan Shafiq (2006)
The main purpose of this research is to assist clinical personnel such as clerk, doctor and nurse to run clinic daily activities through an information system. This research focused on the development of electronic clinic information system application which can give long term benefits to them. This application is developed using the open source software such as Apache Web Server, MySQL Database, phpMyAdmin Database Administrator plus with PHP programming language. Three problems have been identified and researcher focused on how to solve the problems. Those three problems previously done manually and the existence of this application would change the manual processes to computerized processes. Clerk no longer needs to manually count the medicine stock because this application will count all stocks by itself Medication prescription errors could be reduced using the computerized medication prescription to replace the handwriting of doctors. At then end of month, clerk does not need to key-in one by one patient's name into computer to produce invoices and claims for each panel anymore. This application will does it by clicking only one button. Therefore, this application is really hope to reduce burden of clinical personnel and make clinical processes faster than before.